Strategi Komunikasi Master of Ceremony Manten Jawa Di Kelurahan Tanjung Marulak Hilir Kecamatan Rambutan Kota Tebing Tinggi - Nahda Dhiya Irbah; Muhammad Idris; Maryadi (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
This research uses descriptive qualitative method. Qualitative descriptive is focused on answering research questions related to the questions of who, what, where and how an event or experience occurs until finally it is examined in depth to find patterns that emerge in these events.The result of this study is the lack of communication between the Master of Ceremony Manten Javanese and the Javanese community in Tanjung Marulak Hilir Village, which can be seen from the low level of public understanding of Javanese traditional marriages which is characterized by the lack of human resources who can carry out the task of guiding wedding processions, especially as Pranata Adicara.